EDUCATING FOR EMPOWERMENT: ADDRESSING INTIMATE PARTNER VIOLENCE AGAINST WOMEN THROUGH INNOVATIVE INTERVENTIONS - Amira, Ahmed Hassan El-Sayed; Mahmoud , Abdel-Rahman Ali (Research Journal of Health, Medicine and Nursing, 2024)
Intimate Partner Violence (IPV) is a pervasive issue that disrupts the sanctity of home, causing distress and emotional turmoil. IPV encompasses various forms of abuse, including physical, sexual, economic, and emotional violence, perpetrated by current or former partners. This destructive dynamic erodes the foundations of family relationships, affecting the quality of life and the structure of families. While IPV is often associated with men as aggressors against women, it can occur in same-sex relationships and involve female perpetrators. This paper delves into the complexities of IPV, exploring its detrimental impact on individuals and families and addressing strategies for prevention and support.